2015
DOI: 10.1242/jeb.110577
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic models of orangutan hand-assisted alarm calls

Abstract: Orangutans produce alarm calls called kiss-squeaks, which they sometimes modify by putting a hand in front of their mouth. Through theoretical models and observational evidence, we show that using the hand when making a kiss-squeak alters the acoustics of the production in such a way that more formants per kilohertz are produced. Our theoretical models suggest that cylindrical wave propagation is created with the use of the hand and face as they act as a cylindrical extension of the lips. The use of cylindrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Forces propelling cognitive processes would have then compelled vocal progress by association, and vice versa. For instance, with the emergence of theory of mind, individuals would have been able to exploit deceptive calls 34 35 36 , effectively launching new communicative and social dynamics within a population where acoustic deception was previously absent. If vocal and cognitive sophistication developed hand-in-hand over the course of human evolution during the last 10 mya, then, the processes of speech evolution and language evolution could be considered to have been one and the same.…”
Section: Discussionmentioning
confidence: 99%
“…Forces propelling cognitive processes would have then compelled vocal progress by association, and vice versa. For instance, with the emergence of theory of mind, individuals would have been able to exploit deceptive calls 34 35 36 , effectively launching new communicative and social dynamics within a population where acoustic deception was previously absent. If vocal and cognitive sophistication developed hand-in-hand over the course of human evolution during the last 10 mya, then, the processes of speech evolution and language evolution could be considered to have been one and the same.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due, partly, to favourable grounds regarding excluding ecological or genetic causal explanations, as well as issues surrounding the distinction emulation vs. Together with colleagues, we have in fact investigated in detail possibly the single case in primates where this is the case (De Boer et al, 2015;Hardus et al, 2009b;Lameira et al, 2013a). This rare example refers to wild orangutans modifying sound by positioning a hand or by holding detached leaves in front of the lips during vocal production.…”
Section: Why Vocal Traditions Are Differentmentioning
confidence: 99%
“…This ability may provide information that is key to responding appropriately. Indeed, it has been shown that nonhuman animals’ “eavesdropping” on another species alarm calls increases opportunities for survival ( Owings and Morton 1998 ; Kitchen et al 2010 ; Fallow et al 2011 ; de Boer et al 2015 ; Magrath et al 2015 ). Advantageous responses to inter-specific calls may occur as a result of acoustic similarity in the signals ( Aubin 1991 ; De Kort and Carel ten 2001 ; Johnson et al 2003 ).…”
mentioning
confidence: 99%